A study of the major novellas of E.T.A. Hoffmann - Röder, Birgit, 1965- (Studies in German literature, linguistics, and culture., 2003)
Analysis of the novellas of the German Romantic writer and composer, focusing on the issues of art and the artist. The German Romantic writer and composer E. T. A. Hoffmann (1776-1822) - perhaps best known to the English-speaking world through his 'Nutcracker' and through Jacques Offenbach's opera 'Tales of Hoffmann' - struggled to convince his predominantly bourgeois public of the merits of art and literature. Not surprisingly, many of his most important novellas are bound up with the dilemmas of art and the challenges faced by the Romantic artist, and it is these 'Künstlernovellen' that are the focus of this study. Birgit Röderargues that Hoffmann's artists are not simply individuals who create works of art, but rather figures through whom the author explores the predicament of those who reject the conventional world of bourgeois reality and seek to assert the claims of the imagination in a world dominated by prosaic rationalism. Contrary to previous scholars however, Röder demonstrates that Hoffmann's novellas clearly warn against a view of art as an autonomous aesthetic realm cut off from the world of reality. This is particularly apparent in Röder's analysis of gender relations in Hoffmann's oeuvre - especially the relationship between (male) artist and (female) muse - which underlines the extent to which art, literature, and the imagination are inseparably bound up with the prevailing social reality. The novellas that are given extensive consideration are 'Das Fräulein von Scuderi, Der Sandmann, Die Jesuiterkirche in G., Die Fermate, Der Artushof, Don Juan, Das Sanctus,' and 'Rat Krespel'. Birgit Röder teaches German language and literature at the University of Reading, UK.